Association of Vitamin D and Parathyroid Hormone With Barrett's Esophagus. Issue 10 (November 2019) - Rubenstein, Joel H.; McConnell, Daniel; Beer, David G.; Chak, Amitabh; Metko, Valbona; Clines, Gregory
Abstract : Background: Esophageal adenocarcinoma has been inversely associated with exposure to ultraviolet radiation. This could be because of vitamin D deficiency or hyperparathyroidism promoting gastroesophageal reflux disease (GERD) and Barrett's esophagus. Aim: The aim of this study is to determine the association between parathyroid hormone (PTH) and vitamin D deficiency with GERD symptoms, erosive esophagitis, and Barrett's esophagus. Methods: We assayed banked serum for PTH and total 25-hydroxy vitamin D from a cross-sectional cohort. Logistic regression was performed to estimate the associations of vitamin D deficiency and hyperparathyroidism with GERD symptoms, erosive esophagitis, and Barrett's esophagus. Results: Sera from 605 men were assayed, including 150 with GERD, 216 with erosive esophagitis, 145 with Barrett's esophagus, and 174 normal subjects. Contrary to our hypothesis, we found a strong inverse association between Barrett's esophagus and hyperparathyroidism (odds ratio=0.516; 95% confidence interval=0.265, 1.01), and a trend toward an inverse association with vitamin D deficiency. We found no association between vitamin D deficiency or hyperparathyroidism with GERD symptoms or erosive esophagitis. Conclusions: Contrary to our hypothesis, we found an inverse association between serum PTH and Barrett's esophagus. Validation of the finding and the mechanism of that association deserves further study. Abstract : Supplemental Digital Content is available in the text.